Yinqin Qingfei granules alleviate Mycoplasma pneumoniae pneumonia via inhibiting NLRP3 inflammasome-mediated macrophage pyroptosis - Song, Zhe; Han, Chengen; Luo, Guangzhi; Jia, Guangyuan; Wang, Xiao; Zhang, Baoqing (Frontiers in Pharmacology, 2024)
Background: Mycoplasma pneumoniae pneumonia (MPP) is a prevalent respiratory infectious disease in children. Given the increasing resistance of Mycoplasma pneumoniae (MP) to macrolide antibiotics, the identification of new therapeutic agents is critical. Yinqin Qingfei granules (YQQFG), a Chinese patent medicine formulated specifically for pediatric MPP, lacks a clear explanation of its mechanism.The primary components of YQQFG were identified using LC-MS/MS. In vitro, RAW264.7 cells infected with Mycoplasma pneumoniae (MP) underwent morphological examination via scanning electron microscopy. Drug-containing serum was prepared, and its intervention concentration was determined using the CCK-8 assay. The active components of YQQFG were molecularly docked with NLRP3 protein using Autodock Vina software. A RAW264.7 cell line overexpressing NLRP3 was created using lentivirus to pinpoint the target of YQQFG. In vivo, MPP model mice were established via nasal instillation of MP. Lung damage was assessed by lung index and H&E staining. Pyroptosis-associated protein levels in cells and lung tissue were measured by western blot, while interleukin (IL)-1β and IL-18 levels in cell supernatants and mouse serum were quantified using ELISA. Immunofluorescence double staining of lung tissue sections was conducted to assess the correlation between NLRP3 protein expression and macrophages. The expression of the community-acquired respiratory distress syndrome toxin (CARDS TX) was evaluated by qPCR. Results: 25 effective components with favorable oral bioavailability were identified in YQQFG. Both in vitro and in vivo studies demonstrated that YQQFG substantially reduced the expression of the NLRP3/Caspase-1/GSDMD pathway, decreasing the release of IL-1β and IL-18, and inhibited MP exotoxin. Molecular docking indicated strong affinity between most YQQFG components and NLRP3 protein. Lentivirus transfection and immunofluorescence double staining confirmed that YQQFG significantly suppressed NLRP3 expression in macrophages, outperforming azithromycin (AZM). The combination of YQQFG and AZM yielded the optimal therapeutic effect for MPP. Conclusion: YQQFG mitigates inflammatory responses by suppressing NLRP3 inflammasome-mediated macrophage pyroptosis, thereby ameliorating MP-induced acute lung injury. YQQFG serves as an effective adjunct and alternative medication for pediatric MPP treatment.